International origins of social and political theory - Barkawi, Tarak; Lawson, George, 1972- (Emerald Group Publishing Limited, 2017)
This special issue is animated by the necessary entanglement of theory and history, the cortical relationship between theory and practice, and the transboundary relations that help to constitute systems of thought and practice.
Keywords: Sociology.; Social sciences -- Philosophy.; Political science -- Philosophy.; elektronické knihy; electronic books